Pengaruh Edukasi Tentang Pencegahan Wasting terhadap Pengetahuan Ibu Balita di Wilayah Kerja Puskesmas Gedung Aji - Diana Ariyanti; Ade Nurahma Saniban; Resti Vernika Selviana; Hikmah Ifayanti; Sukarni Sukarni; Rika Agustina (Yayasan Jompa Research and Development, 2026)
Wasting remains a serious global health issue, affecting 45 million children, with Indonesia reporting a prevalence of 8.5% in 2023. In Lampung, several areas record rates above 10%, and cases at Gedung Aji Health Center increased from 13.9% (2023) to 15.7% (2024). This condition affects children's growth, cognitive development, and risk of mortality. Although various efforts have been implemented, low maternal knowledge remains a major barrier; therefore, education is essential to shape proper preventive behaviors. The booklet was selected as an educational medium because it has been proven effective in improving mothers’ understanding. This study aimed to determine the effect of wasting prevention education on the knowledge of mothers of children under five at Gedung Aji Health Center in 2025. This research used a quantitative approach with a pre-experimental one-group pretest–posttest design. The population consisted of all 65 mothers of children under five, with a sample of 16 selected through accidental sampling. Data were collected using a questionnaire and analyzed using univariate and bivariate (dependent t-test) methods. The results showed that the average knowledge score before education was 56.8, increasing to 88.1 after education. Statistical testing obtained p < 0.001 (p < 0.05), indicating a significant effect of wasting prevention education on improving maternal knowledge, with an average increase of 31.2%. It is recommended that mothers regularly provide nutritious meals, maintain hygiene, monitor child growth, and seek health services promptly. Health workers are advised to deliver education in simple language, monitor wasting risk, conduct two-way discussions, and provide leaflets as guidance.